(untitled) (Dhaka University Journal of Biological Sciences, 2011)
It is hypothesized that microsatellite locus TH01, which is located in close proximity to beta-globin gene and immune regulatory region in human, plays a role in malaria predisposition. In this study, authors verified the association of microsatelite allele (AATG repeat unit) at TH01 locus with malaria infection. The study provided significant evidence that allele-9 at this locus in P. falciparum infected individual illustrate the genetic predisposition towards the disease. Moreover, the predominance of allele-9 at TH01 in the individuals inhabiting malaria endemic area suggests that genetic predisposition towards malaria is an archaic phenomenon. Key words: Microsatellites; Allele; Genotype; Locus, Malaria DOI: http://dx.doi.org/10.3329/dujbs.v20i1.8831 Dhaka Univ. J. Biol. Sci. 20(1): 1-6, 2011 (January)